Nutrient Recovery from Agricultural Waste Water Using Electrocoagulation Process, A Case Study of Thekelan, Semarang, Indonesia - Mochamad Arief Budihardjo; Sudarno Sudarno; Ika Bagus Priyambada; Amin Chegenizadeh; Purwono Purwono (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2023)
Eutrophication is a natural phenomenon in aquatic ecosystems that causes algae and other aquatic plants to overproduce. This process can benefit the ecology in tiny amounts, but too many nutrients can generate hazardous algal blooms and kill fish and other aquatic life. To prevent eutrophication and sustain aquatic ecosystems, agricultural waste water like microalgae production wastewater must be treated. The goal of the project is to get nitrogen and phosphorus out of the wastewater from growing microalgae, which is an agricultural waste water. One way to recover nutrients from wastewater is electrocoagulation. This procedure uses an electric current to create microscopic gas bubbles that collect and remove pollutants from wastewater. According to this study, electrocoagulation reduces phosphate and nitrate in microalgae culture wastewater. Phosphate concentration dropped by 90.20% in the 15th minute, while nitrate concentration dropped by 36.19% in the 30th minute. These reductions may be caused by struvite formation and nitrate conversion to nitrogen gas. This study demonstrates that electrocoagulation is a potential technology for recovering nutrients from agricultural waste water and reducing aquatic ecosystem eutrophication.